STUDY THE HISTOLOGICAL LESIONS THAT INDUCED BY SHIGELLA FLEXNERI FOR AND THE ROLE OF ANTHEUM GRAVEOLENS AND TO TREATMENT IN COMPARATIVE WITH AN ANTIBIOTIC - Ateen Amer Hameed Al-Azawee; Aziz Khalid Hameed; Hala Mohammed Majeed (Basrah Journal of Veterinary Research)
The present study was carried out to investigate the histological lesions andmorphological changes caused by the experimental Shigella flexneri bacteria in both thesmall intestine and the large intestine in albino mice Musmusculus and attempt to treat themusing the Antheum graveolens and antibiotic amikacin. And study the inhibitory activity ofthe extract of the plant in vitro. Shigella flexneri was tested for a variety of antibiotics andshowed that it was sensitive to (Amikacin, ErythromycinTobramycin,Gentamycin,Ceftriaxone,Cefotaxime and Naldixic acid ) and resistant to(Ampicillin, Trimethoprim and Aztreonam) . The inhibitory activity test was performed ofAntheum graveolens extract toward Shigella flexneri and was found to be sensitive andhigh. Both ID-50 and LD-50 LD dose were determinated. In the present study, thelaboratory animals were divided into 36 mice and randomly assigned to 6 groups. Eachgroup consisted of six mice.These groups are control group, ID-50 group,LD-50 group,group that treated with water Antheum graveolens,group that treated with alcoholicAntheum graveolens and antibiotic group . The bacterial infection of the mice was inducedby mouth ,the animals left dosage of the doses pathogenic from bacteria for a four-day andthe appearance of the disease. On the fourth day, The results of the histological examinationof the small and large intestines showed satisfactory changes in the different tissue layers ofthese structures. microscopic examination showed less enhancement in groups thattreatment with alcoholic Antheum graveolens and antibiotic compared with groups thatadministrated water Antheum graveolens